HPB P41 Pitfalls in establishing a preoperative diagnosis; correlating the radiological and histopathological findings of suspected intraductal papillary neoplasm of the bile duct (IPNB). (7th December 2022) - Hughes, Daniel; Turaga, Sanchit; Gordon-Weeks, Alex; Fryer, Eve; McWeeney, Doireann; Bungay, Helen; Silva, Michael
Abstract: Background: Intraductal papillary neoplasm of the bile duct (IPNB) represents a cohort of uncommon biliary tract tumours. It is commonly unrecognised or misdiagnosed in cross sectional imaging of the liver. This rare tumour is of significant clinical importance as it serves as a pre-cursor lesion for Cholangiocarcinoma. The diagnostic work up of a patient with a suspected IPNB remains predominantly based on imaging and as of yet no consensus has been achieved regarding the optimal diagnostic algorithm. The aim of this study was to compare the radiological and clinico-pathological features of patients with confirmed or suspected IPNB managed in a single tertiary center. Methods: Retrospective review of a departmental database of consecutive patients with suspected IPNB was performed. Clinical information regarding patient demographics, disease presentation, radiological imaging characteristics and histo-pathological features was analysed. Results: Eighteen patients with suspected IPNB were noted, of which histological confirmation was present in eight cases (62%). The most frequent presentation of IPNB was of an incidental finding (50%). The diagnosis of IPNB was made following MRI in 63% of cases. Invasive adenocarcinoma was present in five patients (63%). In the remaining three patients, low grade dysplasia was noted within their IPNB tumours. Conclusions: IPNB is frequently associated with concurrent invasive malignancy. Observation alone is insufficient. Radiological assessment of these tumours remains as the fundamental investigation for diagnosis. However, without confirmatory histology perioperatively, the diagnosis cannot be assured therefore the decision for management must be based upon a patient-centered discussion and a careful evaluation of risk.